Differences between musicians and athletes in personal characteristics: mental toughness, imagery and personality - Budnik-Przybylska, Dagmara; Huzarska-Rynasiewicz, Izabela; Jurek, Paweł; Przybylski, Jacek (Frontiers in Psychology, 2025)
IntroductionIt appears that music and sports share many common elements. However, it turns out that mental toughness and imagery are present in both musicians and athletes, but they are understood and conceptualized differently within these domains. The aim of the study was to explore the relationship between mental toughness, personality, and imagery in two unique groups.MethodsThe sample consisted of a group of athletes (N = 164, 82 females and 82 males) and a group of musicians (N = 97, 61 females and 36 males), aged between 13 and 46 (M = 23.65; Median = 21), with varying levels of experience. The participants filled in the Imagination in Sports Questionnaire, the Short Scale of Mental Toughness in Sport Questionnaire-19, and the Big Five Inventory—Short, with indicators adjusted to both research groups. The results proved significant differences between the two groups.ResultsOur findings indicated that musicians tend to exhibit lower levels of mental toughness compared to athletes. Additionally, musicians demonstrated reduced conscientiousness but higher levels of neuroticism and openness to experiences, as opposed to athletes. In the group of musicians, mental toughness was associated with lower extraversion, neuroticism, higher levels of agreeableness, and lower physiological feelings in imagery. Mentally tough athletes were characterized by lower neuroticism and higher situational and general imagery. Personality and imagery explained 21% of the variance in mental toughness among athletes and 37% among musicians. Neuroticism was the main predictor in both groups. Imagery, however, predicted mental toughness only in the athletes’ group.DiscussionThe comparison of the unique groups brings a fresh perspective on theoretical and practical work in terms of individual differences, confirming the need of creating mental toughness-building interventions in mental preparation for performance in both music and sports.